El comportamiento de la agricultura en la crisis internacional. Resultados a fines del 2009 - Barrientos Felipa, Pedro (2010)
The behaviors of the global economy in the last years of the first decade of this century affected the development of sectors of the economy. One such sector is agriculture, which in turn has a modern, export–oriented one; while the traditional one supplies mostly the local market. Agriculture is of great importance for the country. Not only for what it produces, but by the workforce that it employs This article seeks to expose sources of information to identify how the agricultures is facing the crisis and what were the consequences. In this sense, it exposes the performance of the various types of crops, where each has its own behaviour and exhibit positive results, but we must continue to monitor international buyers and bidders. The initial conclusion states that agriculture can be affected by the crisis and exhibits positive results, but its effect is not as significant as can be observed in others sectors.